SEORANG WANITA 78TAHUN P8A0 SUSPECT CA SERVIKS: A 78-year-old Woman P8A0 With Suspect Cervical Cancer - Rahmi Kurniasih; Aries Hartato (Synergy : Jurnal Ilmiah Multidisiplin, 2023)
Cervical cancer is a primary malignant tumor originating from the cervical canal and / or portio. This is the fourth cancer most commonly diagnosed in women in 2012, with an estimated 527,600 new cases worldwide. With increasing population and aging, the number of cervical cancer cases is expected to increase 1.5-fold by 2030. This cancer will talk about cervical epithelium, where epithelial cells will change the multiplication and change the anatomy of the pathology. Cervical virus is caused by infection with Human Papilloma Virus (HPV). HPV is a DNA virus that is classified based on DNA sequences and divided into high and low oncogenic. Infection of hrHPV into the cervical epithelium causes changes in the host genome, which causes differences in tumor suppressor factors on one side, and induces a function that deviates from various tumor trigger factors on the other side. Clinical symptoms in cervical cancer are early symptoms and advanced symptoms. Therapy in cervical cancer patients is determined by the stage.